Da teoria dos atos de discurso e o problema de Cohen - Souza, Euclides Barbosa Ramos de (2021)
The theory of speech acts was founded by John Langshaw Austin after a compilation of his lectures in the book How to Do Things with Words (1962) and with it we have elucidated that the language is capable of much more than a simple description of the world, for it has also the capacity to perform actions and generate events in the world by means of enunciations and these actions and events could not have another origin besides these acts of language. However, the theory of speech acts was too limited and in a certain way imprecise and only in the future, with the works of John R. Searle and Daniel Vanderveken (Foundations of Illocutionary Logic, 1985) this theory has received a logical and formal treatment, bringing a much more detailed analysis of the notion of illocutionary act, mainly on respect to its illocutionary force and its fundamental components, furthermore the notions of conditions of success (conditions that the speaker has to obtain to perform an illocutionary act with success) and conditions of satisfaction (conditions that has to be obtained in the world for the objective of the speaker be fulfilled). A curious problem emerged on the theory before these improvements and this change, naturally, was already sufficient to solve it. William Lycan (2008) formalized this impasse based on criticisms to Austin by J. L. Cohen in his article Do Illocutionary Forces Exist? and called it Cohen's problem. Basically, this problem concerns an apparent lack of commitment by the speaker with his statement when he begins with the preface “I declare that...”, making it appear that he is making a performative declaration instead of a simple statement about the world. The current theory of speech acts will classify it as a fallacy, because from an attempt to perform an illocutionary act whose force is declaratory it should not be deduced that such an attempt is satisfied, that is, that the act was performed (that all conditions of happiness - conditions of success and satisfaction - were fulfilled, in the context of enunciation).